PENGARUH PARAMETER DENGAN BESARNYA GETARAN TERHADAP KEKASARAN PERMUKAAN PADA PROSES GERINDA SILINDRIS MENGGUNAKAN MATERIAL BAJA S45C - Mei Adi Saputra Adi; Muhamad Riva’i; Indra Feriadi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Cylindrical grinding is a fundamental process in final machining, as it requires high dimensional accuracy and low surface roughness. The purpose of this study was to determine the value of vibration on surface roughness in the cylindrical grinding process. The method used is the Taguchi method. Variations in cylindrical grinding process parameters include workpiece rotation speed and cutting depth. This research shows thatThe faster the rotation of the workpiece and the depth of cutting, the higher the vibration and surface roughness, so that you know the amount of vibration that causes the level of surface roughness in S45C steel material.